Pembelajaran Berbasis Multimedia: Upaya Memahami Keberagaman Gaya Belajar Anak - Harpan Reski Mulia (Jurnal Penjaminan Mutu, 2019)
This writing discusses about a way to understand the varieties of children’s learning styles in environment of formal school. One of the ways that will be discussed is by designing a learning based on multimedia. The research uses an approach which vies some concepts existed in the variable. It is called by library research. The result of this research shows that children’s learning styles generally are divided into three styles, they are auditory, visual, and kinesthetic. By using multimedia approach in teaching, it will help teacher in understanding various styles of children’s learning. It is because of multimedia consist of the components, such as media and audio media and visual media have been integrated in multimedia. Instead of multimedia which is designed well can stimulate children’s attention in learning process so the children are interested to follow the learning and all of aspects that are needed by children.